Development of Maths Module on Measurement Using Digital Flipbook in Elementary School - Azizah, Faiqotul Isma; Asiya, Siti; Wahyuni, Indah (Universitas Pendidikan Indonesia, 2025)
Rapid technological developments encourage innovation in teaching materials, including the transfer of printed modules into electronic modules (e-modules). E-modules can present structured teaching materials in electronic format, including audio, visual, and audio-visual media that can increase student learning motivation. However, the use of e-modules in primary schools is still limited. This study aims to develop a digital flipbook-based electronic module (e-module) on measurement material to increase the learning motivation of grade 1 students at MI Mambaul Ulum Kandangrejo-Jember. The research method used Research and Development (RD) with the ADDIE model. The e-module development was conducted at MI Mambaul Ulum Kandangrejo-Jember. Data were collected through validation by media, language, and material experts. The small-scale implementation test involved 5 students, while the large-scale involved 12 students. The results of media expert validation showed a very feasible category with a percentage of 84.80%, material expert validation was also very feasible with a percentage of 81.60%. The small-scale implementation test obtained a result of 90.75% (very feasible), while the large scale was 86.90% (very feasible). Based on these data, it can be concluded that the digital flipbook-based e-module on measurement material to increase the learning motivation of grade 1 students at MI Mambaul Ulum Kandangrejo-Jember is in the category of very feasible and effective to use in learning.